Shear Behavior of the Interface Between Rock and Cemented Backfill: Effect of Curing Stress, Drainage Condition and Backfilling Rate - Fang, Kun; Fall, Mamadou (Rock mechanics and rock engineering, 2020)
In situ parameters, for example curing stress, drainage conditions as well as backfilling rate, have substantial effects on the geotechnical properties and stability of cemented paste backfill (CPB), which is an evolutive cemented soil mainly used for underground mine support. An in-depth knowledge of the shear characteristics of the interface between CPB and rock is important for the cost-effective and safe design of underground CPB structures. But, no studies to date have investigated the effects of curing stress, drainage conditions and backfilling rates on the shear characteristics of the interface between CPB and surrounding rock mass. Hence, an experimental study is performed to assess the influence of curing stress (0 kPa, 50 kPa, and 150 kPa), drainage conditions (drained and undrained) and backfilling rate (20 kPa/3 h, 30 kPa/3 h, and 40 kPa/3 h) of CPB on the shear characteristics (behavior, properties) of the interface between CPB and rock. It is found that higher curing stress and backfilling rate contribute to the shear strength development of the studied interface because of the increased effective stress and matrix suction at the interface. Moreover, in comparison to undrained condition, the drained condition contributes to the shear strength acquisition at the interface. The findings provide technical information for improving the stability analysis of backfill structures and are practically important for opening barricades and designing filling sequences.